Critical Synthesis Package: Mental Illness Clinicians' Attitudes Scale (MICA) - Ayesha Siddiqua; Adriana Foster (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Mental Illness Clinicians' Attitudes (MICA) Scale, and (2) a copy of the MICA-2 Scale, MICA-4 Scale, and MICA manual developed by Prof. Graham Thonicroft, Aliya Kassam, and the Health Service and Population Research Department, Institute of Psychiatry, King's College London. The MICA Scale is a short, self-administered instrument developed to assess attitudes about psychiatry and people with mental illness. The MICA-2 Scale is suitable for application to medical students, while the MICA-4 Scale is suitable for nurses, as well as health and social services professionals. Both versions of MICA Scale have 16 items and users indicate their responses on a 6-point Likert-type scale. The score ranges between 16 and 96 and is the sum of the individual item scores. A high overall score indicates a more negative attitude. MICA Scale has been demonstrated to be a valid scale and responsive to various interventions. Studies have been conducted on samples with different geographical, social, and cultural backgrounds. Two studies demonstrated that the MICA-2 and MICA-4 items group into five domains: Views of Mental Illness and Psychiatry, Knowledge of Mental Illness, Disclosure, Distinguishing Mental and Physical Health Care, and Patient Care for people with Mental Illness. Of these, Views of Mental Illness and Psychiatry Disclosure have high internal consistency. The internal consistency of the scale as a whole is high. The scale has adequate convergent validity based on its correlation with instruments designed to assess the emotional reactions and social proximity to people with mental illness. The MICA-2 and MICA-4 Scales were responsive to changes in attitudes about mental illness and psychiatry after interventions. The scales fill a gap in the domain of attitudes assessment for health professionals, particularly for medical students and physicians, especially as interventions targeting stigma towards people with mental illness are becoming an integral part of medical training curricula.